Host diversity can reduce potato late blight severity for focal and general patterns of primary inoculum - Mundt, C. C.; Garrett, Karen A. (My University, 2007)
The use of host diversity as a tool for management of potato late blight has not been viewed as promising in the past. But the increasing importance of late blight internationally has brought new consideration to all potential management tools. We studied the effect of host diversity on epidemics of potato late blight in Oregon, where there was little outside inoculum. The experimental system consisted of susceptible potato cv. Red LaSoda and a highly resistant breeding selection, inoculated with local isolates of US-8 Phytophthora infestans. Potatoes were grown in single-genotype plots and also in a mixture of 10 susceptible and 26 resistant potato plants. Half of the plots received inoculation evenly throughout the plot (general inoculation) and half received an equal quantity of inoculum in only one corner of the plot (focal inoculation). The area under the disease progress curve (AUDPC) was greater in single genotype stands of susceptible cv. Red LaSoda inoculated throughout the plot than with stands inoculated in one focus. The host-diversity effect on foliar late blight was significant in both years of the investigation; the AUDPC was reduced by an average of 37% in 1997 and 36% in 1998, compared with the mean disease level for the potato genotypes grown separately. Though the evidence for influence of inoculum pattern on host-diversity effects was weak (P = 0.15), in both years there was a trend toward greater host-diversity effects for general inoculation. Statistical significance of host-diversity effects on tuber yield and blight were found only in one of the two years. In that year, tuber yield from both the resistant and susceptible cultivar was increased in mixtures compared with single genotype stands and tuber blight was decreased in mixtures for susceptible cv. Red LaSoda.
Citation: Garrett, K., Mundt, C. (2007). Host Diversity Can Reduce Potato Late Blight Severity for Focal and General Patterns of Primary Inoculum. Phytopathology, 90(12), 1307-1312. https://doi.org/10.1094/PHYTO.2000.90.12.1307
Keywords: Host diversity; Potato late blight; Cultivar mixtures; Genetic diversity; Spatial pattern of inoculum; Variety mixtures